Settlement of Sharia Business Disputes Through the National Sharia Arbitration Board (BASYARNAS) - Mochamad Imron (Al-Mahkamah: Islamic Law Journal, 2025)
The National Sharia Arbitration Board (BASYARNAS) is an arbitration institution that has the authority to resolve sharia business disputes. BASYARNAS has its own arbitration procedural law which can be used as a legal option for the disputing parties as regulated in the BASYARNAS Procedural Regulations. However, to apply for sharia business dispute resolution through BASYARNAS, the applicant must remain based on the arbitration clause or arbitration agreement. This research is normative research with descriptive research type. The approach used is applied normative. Data collection was carried out by literature study. The data used is primary data and secondary data. Secondary data consists of primary legal materials, secondary legal materials, and tertiary legal materials. The collected data was then analyzed qualitatively. The research results show that the legal basis used in resolving disputes through BASYARNAS is Islamic law and national law. The BASYARNAS Procedure Regulations regulate the legal basis used, namely the Al-Qur'an, As-Sunnah, Ijma', Law no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, MUI Decree, and DSN-MUI Fatwa. The parties who have agreed to resolve their disputes at BASYARNAS will be resolved and decided according to BASYARNAS procedural rules. The procedure for resolving disputes through BASYARNAS is as follows: request for arbitration, appointment of a single arbitrator or panel of arbitrators, response from the respondent, conciliation, witness or expert evidence, withdrawal of the application, decision, registration of the decision, and execution of the BASYARNAS decision. The supporting factor in resolving sharia business disputes through BASYARNAS is that BASYARNAS arbitrators are competent arbitrators in their field. Meanwhile, the inhibiting factors in resolving sharia business disputes through BASYARNAS are resistance from third parties, resistance from the executed party, requests for judicial review (PK), unclear rulings, and the object of execution is state property.